Assessing the potential for Atlantic salmon (Salmo salar) colonization of Nunavik’s Arctic and subarctic rivers by 2070–2100 - P. Poulin; A. St-Hilaire; C. Boyer; N. E. Bergeron (Arctic Science, 2025)
In Nunavik, Québec, Canada, Atlantic salmon (Salmo salar) populations reach their northern limit in four rivers of southern Ungava Bay. With projected river warming from climate change, this study assesses the potential for Atlantic salmon to colonize new rivers in Nunavik by modelling water temperatures and evaluating river accessibility. Migration barriers were identified with a literature review, topographic data, and satellite imagery. Water temperatures were modelled with a generalized additive model using ERA5-Land air temperature, observed daily mean temperatures, and water surface temperature estimated from Landsat imagery. Our projections indicate an average increase of the rivers mean summer temperatures of 1.2–2.7 °C by the end of the century, enhancing thermal conditions in current salmon rivers with more days with optimal growth temperatures (16–20 °C) while still having limited days with thermal stress (>22 °C). By 2100, other Ungava Bay rivers may be colonized, as most are accessible and expected to reach more suitable temperatures. However, Nunavik’s northernmost rivers would remain too cold and colonization of the Hudson Bay watershed appears less likely due to the inaccessibility of most rivers and their distance from established anadromous populations.